(untitled) - Cameronm, Robert (San Francisco, 1980)
Alistair Cooke is a journalist and broadcaster. Cooke was born in Manchester, England on November 20, 1908. He obtained his education at Cambridge, Yale, and Harvard. His career is based on his observations of American life and culture. Cooke worked as a correspondent for NBC and as a special correspondent for the London Times and the Guardian. He is perhaps most famous for his BBC weekly broadcast, "Letter From America," which has been successful for over fifty years because of its sophisticated wit. Cooke became well-known in the United States as host for Omnibus for nine years and later as host of the Masterpiece Theatre. He has also written numerous books including the bestsellers Alistair Cooke's America, Six Men, and Fun and Games with Alistair Cooke. In 1973, Cooke was made an honorary Knight of the British Empire.
Keywords: Above photos,Ảnh trên không; London,London